2021
DOI: 10.3389/fphar.2021.707335
|View full text |Cite
|
Sign up to set email alerts
|

Diarylpentanoid (1,5-bis(4-hydroxy-3-methoxyphenyl)-1,4-pentadiene-3-one) (MS13) Exhibits Anti-proliferative, Apoptosis Induction and Anti-migration Properties on Androgen-independent Human Prostate Cancer by Targeting Cell Cycle–Apoptosis and PI3K Signalling Pathways

Abstract: Diarylpentanoids exhibit a high degree of anti-cancer activity and stability in vitro over curcumin in prostate cancer cells. Hence, this study aims to investigate the effects of a diarylpentanoid, 1,5-bis(4-hydroxy-3-methoxyphenyl)-1,4-pentadiene-3-one (MS13) on cytotoxicity, anti-proliferative, apoptosis-inducing, anti-migration properties, and the underlying molecular mechanisms on treated androgen-independent prostate cancer cells, DU 145 and PC-3. A cell viability assay has shown greater cytotoxicity effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 148 publications
(173 reference statements)
0
6
0
Order By: Relevance
“…In addition, curcumin has been reported to induce apoptosis in CRC cells via the upregulation of caspase-3 and downregulation of Bcl-2 protein [ 92 , 93 , 94 , 95 ]. Numerous curcumin analogues have been reported to promote apoptosis in cancer cells by inducing caspase-3 cleavage/activity and Bcl-2 protein suppression [ 63 , 96 , 97 , 98 , 99 ]. For instance, our group also reported another curcumin analogue MS13 significantly promoted caspase-3 activity and downregulated Bcl-2 protein expression in SW480 and SW620 cells [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, curcumin has been reported to induce apoptosis in CRC cells via the upregulation of caspase-3 and downregulation of Bcl-2 protein [ 92 , 93 , 94 , 95 ]. Numerous curcumin analogues have been reported to promote apoptosis in cancer cells by inducing caspase-3 cleavage/activity and Bcl-2 protein suppression [ 63 , 96 , 97 , 98 , 99 ]. For instance, our group also reported another curcumin analogue MS13 significantly promoted caspase-3 activity and downregulated Bcl-2 protein expression in SW480 and SW620 cells [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The different morphological criteria were used to clarify healthy live cells, early or late apoptotic and necrotic cells based on reference protocols as previously described [ 63 , 268 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of morphological observations, increased caspase-3 activity, and reduced Bcl-2 protein levels in these cells, the authors concluded that curcumin A induces apoptosis and inhibits DU 145 and PC-3 cell migration. They suggested that the curcumin A anticancer activity is due to the modulation of the differentially expressed genes (DEGs) associated with the cell cycle apoptosis and PI3K pathways [43]. Additionally, Tajuddin and co-workers reported that curcumin A (10) exhibits a higher inhibitory effect on two types of non-small-cell lung cancer (NSCLC) cells-squamous cell carcinoma (NCI-H520, EC 50 = 4.7 ± 0.1 µM) and adenocarcinoma (NCI-H23, EC 50 = 3.7 ± 0.4 µM)-compared to curcumin (NCI-H520, EC 50 = 25.2 ± 1.7 µM; and NCI-H23, EC 50 = 18.5 ± 0.7 µM).…”
Section: Anticancer Activitymentioning
confidence: 99%
“…On the basis of morphological observations, increased caspase-3 activity, and reduced Bcl-2 protein levels in these cells, the authors concluded that curcumin A induces apoptosis and inhibits the DU 145 and PC-3 cell migration. They suggested that the curcumin A anti-cancer activity is due to modulation of differentially expressed genes (DEGs) associated with the cell cycle-apoptosis and PI3K pathways [36]. Additionally, Tajuddin and co-workers reported that curcumin A (10) exhibits higher inhibitory effect on two types of non-small cell lung cancer (NSCLC) cells -squamous cell carcinoma (NCI-H520, EC50 = 4.7±0.1 μM) and adenocarcinoma (NCI-H23, EC50 = 3.7±0.4 μM) -compared to curcumin (NCI-H520, EC50 = 25.2 ± 1.7 μM; and NCI-H23, EC50 = 18.5 ± 0.7 μM).…”
Section: Anticancer Activitymentioning
confidence: 99%